Trends in Low-Density Lipoproteins Cholesterol (LDL-C) in US Aged 12 to 80 Years: Data from the 2007-2018 National Health and Nutrition Examination Survey (NHANES) - Wang, Inga; Hou, Stephen; Rahman, Mohammad H; Li, Xiaoyan; Ritchie, David; Spector, Antoinette L (Journal of Neurology and Epidemiology, 2022)
Background: Elevated levels of low-density lipoprotein cholesterol (LDL-C) are associated with an increased risk of coronary heart disease. Objectives: We described LDL-C distributions across the age span and compared the trends in three distinct cross-sectional surveys during 2007-2010, 2011-2014, and 2015-2018. Methods: This is an observational study. Blood lipid measurements, taken from 40,977 noninstitutionalized participants, aged 12 to 80, were obtained from the National Health and Nutrition Examination Survey (NHANES) study. Results: The LDL-C values changed by age and differed by sex. Mean LDL-C levels increased with age through middle age and then decreased with age. In males, mean LDL-C declined from 104.5 (95% CI, 103.6-105.3) in 2007-2010, to 100.5 (95% CI, 99.7-101.4) in 2011-2014, and 100.8 (95% CI, 99.9-101.7) in 2015-2018 (p<0.001 for linear trend). In females, mean LDL-C declined from 110.3 (95% CI, 109.5-111.1) in 2007-2010, to 108.3 (95% CI, 107.6-109.1) in 2011-2014, and 106.8 (95% CI, 105.9-107.7) in 2015-2018 (p<0.001 for linear trend). Conclusions: Between 2007 and 2018, favorable trends in LDL-C levels were observed among noninstitutionalized residents in the US.